Socialization of PBB-P2 Receivables Collection in Tegal Regency - Amirah; Mohammad Arridho Nur Amin; Sri Murdiati; Juli Riyanto Tri Wijaya (Yayasan Cendekiawan Digital Indonesia, 2024)
One of the problems that is often faced by Land and Building Taxpayers (PBB-P2) in paying taxes is the amount of PBB-P2 payments owed. To be able to find out the amount of the outstanding PBB-P2 payment, it is necessary to understand the tax subject, tax object, tax object exemption, and the PBB-P2 rate owed. Through Community Service, it is hoped that the Village Head as a Taxpayer can understand the amount of payments that must be paid to the outstanding PBB-P2 and provide socialization to the villagers so that taxpayers from various villages in Tegal Regency can obey in paying PBB-P2. Thus, through this service, it will provide understanding to the participants to be able to pay tax arrears and be obedient in paying taxes afterwards. The target of this service is the Village Head of Tegal Regency. This activity will be held on Tuesday, August 13, 2024 at 09.00 WIB until it is finished. The results of the service activities showed that there was an increase in understanding of PBB-P2 tax subjects, tax objects, exemptions for PBBP2 tax objects, filling out tax object notification letters (SPOP) to the calculation of urban rural land and building taxes (PBB-P2) and the taxes collected could be implemented properly.